c.1 - Reddy , D. Narasimha (ed.) (New Delhi, 2009)
This book is largely an outcome of the papers presented at the National workshop on 'Land Markets and Rural Poverty' organized by the Center for Rural Studies, Lal Bahadur Shastri National Academy of Administration, Mussoorie. The book also incorporated a few research papers on similar and related issues by eminent administrators and technocrats. Examining the potential of the 'Land' question in alleviating rural poverty, the contributors addressed the strategies for rural development, poverty alleviation, the issues of volatility in land markets and agrarian reforms.
Keywords: Land Reform